ANALISIS KEBIJAKAN WORK FROM HOME TERHADAP EFEKTIVITAS KINERJA PEGAWAI: STUDI KASUS PADA PERUSAHAAN BERBASIS TEKNOLOGI DI YOGYAKARTA - Edison Jaya Kusuma edison; Priyastiwi Priyastiwi; Rufaida Setyawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to analyze the impact of the work from home (WFH) policy on employee performance effectiveness in a technology-based company. The background of this research lies in the significant shift in work patterns since the pandemic, which has forced companies to adapt their work systems to remain both productive and flexible. A qualitative case study approach was applied, involving in-depth interviews, observations, and document analysis. The data were processed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the WFH policy positively influences working time flexibility, work-life balance, and employee motivation. Nevertheless, several challenges emerged, particularly in terms of communication, team coordination, and limited direct supervision by managers. Supporting factors of effective performance under WFH include the utilization of communication technology, adaptive organizational culture, and managerial support. Conversely, obstacles consist of technical difficulties, unequal workload distribution, and the potential decline in employee discipline. This research concludes that WFH policies can enhance employee performance effectiveness when supported by adequate technological infrastructure, clear managerial policies, and a trust-based work culture. The practical implication of this study is that companies should design a balanced hybrid working model that combines WFH and work from office (WFO) to maintain both productivity and employee satisfaction.